Efisiensi Pada Sepeda Listrik Dengan Dinamo Sepeda Sebagai Generator - Fathan Mubina Dewadi (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
This research refers to the advantages of a bicycle dynamo over an electric bicycle, namely its ability to save fuel. Because this type of vehicle only uses electric current as fuel. Their low prices and similar models of motorbikes ensure that there is no difference between an electric bicycle and a fossil fuel motorbike. Electric vehicles have developed, ranging from two-wheeled, four-wheeled, trains, to carts paired with electric motors that use batteries. The method is done manually and takes the essence of several related references then takes the supporting equations so that it becomes a research innovation in generating a research innovation. Do not forget to also conduct a comparative study of this research with previous research. Research optimization by adding a bicycle dynamo as a generator can save power up to 0.05 What a distance of 300 m. It is proven in research at a distance of 300 m, an E-Bike that uses a bicycle dynamo costs only Rp.4.14 / 300m, an E-Bike that uses a transformer costs Rp.4.2 / 300m. Electric power at a distance of 300 m with a bicycle dynamo consumes 271.59 W while electric power at a distance of 300 m with a step-down transformer consumes 295.02 W, and it is proven that bicycle dynamos are more efficient in consuming electrical energy.